Pengaruh Pernikahan Dini Terhadap Tingkat Perceraian Di Kecamatan Panti - Balqis, Antika; Qomariyah, Nur Avivatul; Nurlailia, Yuniarti; Fitriana, Ani Qotuz Zuhro’ (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
This study aims to find out what are the factors in the occurrence of early marriage in the Panti District and also to find out what are the influences of early marriage on the divorce rate that occurs in the Panti District. This study uses quantitative research methods with the type of data that is collected as primary data. The results of the research show that early marriage is a marriage carried out by every individual whose age is not enough to marry, namely under 19 years. Which when someone is not yet 19 years old is considered not mature enough physically and psychologically. there is also what is a factor in the occurrence of early marriage, which consists of internal factors and external factors. The internal factor is due to the will of the family, family conditions, self-will, it could also be due to customs. While the external factors are caused by pregnancy out of wedlock and also economic factors. Related to the problem of the effect of early marriage on the divorce rate in Panti District, it has a significant influence. The number of divorces from couples who married at an early age in the Panti District was 31 people from 2021 to 2022 where the number of early marriages was higher in 2022. Meanwhile, the number of couples who divorced at an early age was even greater in 2022 due to factors economy. This means that the divorce rate is also higher than the previous year, estimated at 1%.